Use of Surface Imaging in Combination With IGRT for Proton Beam Craniospinal Irradiation (CSI) Setup - Liu, C; Gao, M; Wang, H; Pankuch, M (International journal of radiation oncology, biology, physics, 2021)
PURPOSE/OBJECTIVE(S)Proton Beam Craniospinal Irradiation (CSI) requires multiple isocenters to cover the entire brain and spine target. These matching fields can lead to treatment field overlap or gap to yield dose heterogeneity. To ensure acceptable dose heterogeneity, we previously acquired KV-images at all isocenters to adjust patient posture before treating the first brain field. This process requires extra setup time and additional radiation exposure to the patient. We present a novel setup workflow using surface imaging in combination with IGRT to reduce the number of KV-images for proton CSI setup.MATERIALS/METHODSThe patient is first setup at the cranial isocenter where head position is confirmed with KV-imaging. The lower body posture is adjusted based on guidance from the surface imaging system. The patient is shifted to lower isocenters where spine position can be fine-tuned with KV imaging if needed. The residual corrections, i.e., shifts required per KV-imaging after using surface imaging guidance, are recorded. If spine position determined by the surface imaging is within set-up tolerance verified by the X-rays for the first three fractions, we will no longer shift patient and verify spine isocenters with KV-imaging before treating the brain field. We will only verify setup by KV-imaging before each field delivery.RESULTSSetup of 127 treatment fractions were analyzed. The setup method is found to be beneficial for 9 out of 13 proton CSI patients. Among the 9 patients using surface imaging, the average magnitude of the residual shifts for X, Y, and Z directions were 0.17 ± 0.15 cm, 0.24 ± 0.18 cm, and 0.14 ± 0.16 cm respectively. The average KV-imaging count was reduced from 8 to 5 per fraction with reduced setup time. For surface imaging, the reference surface image auto-generated from planning CT images was found to be accurate, however, one may request an in-room setup capture due to the change of correlation between the skin and the bony anatomy. Setup using surface imaging for patients with high body mass index is less accurate due to the poor correlation between surface and bony anatomy.CONCLUSIONFor proton CSI, while setting up the patient for the brain and cervical spine treatment, surface imaging provides a useful guidance for the setup of the spine. Overall, surface imaging provides a larger field of view than KV-imaging with no additional imaging dose. For treatment with target size larger than imaging field, surface imaging can potentially reduce the amount of setup images thus reduce imaging dose and increase setup efficiency.